The effect of grade retention on performance in Spanish students: a propensity score matching approach - Jaime León; Fernando Martínez-Abad (Large-scale Assessments in Education)
Abstract Background Grade retention is an educational aspect that concerns teachers, families, and experts. It implies an economic cost for families, as well as a personal cost for the student, who is forced to study one more year. The objective of the study was to evaluate the effect of course repetition on math, science and reading competencies, and math self-efficacy. Methods We employed a causal approach using propensity score matching to compare the result in the PISA tests of retained versus non-retained students. We found a comparison group with a similar distribution in the control variables to the group of retained students. Results Course retention has a negative effect on the academic performance of students. Retained students showed lower results in math, science, reading, and math self-efficacy compared to the non-retained group. Conclusions In line with previous research, evidence shows that grade repetition in Spain is not obtaining the expected results in retained students. This evidence suggests a rethinking of grade retention policies in Spain.